2017
DOI: 10.1371/journal.pone.0186831
|View full text |Cite
|
Sign up to set email alerts
|

Early resumption of sexual activity following voluntary medical male circumcision in Botswana: A qualitative study

Abstract: Unprotected sexual intercourse after undergoing voluntary medical male circumcision but prior to complete wound healing can lead to major adverse events including HIV acquisition. To better understand perceptions related to early resumption of sex prior to wound healing, 27 focus group discussions were conducted among 238 adult men, women, and community leaders in Botswana. Median age among all participants was 31 years of whom 60% were male and 51% were either employed and receiving salary or self-employed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
2
3
0
1
Order By: Relevance
“…However, a significant proportion of the women in this study did not have adequate knowledge of the six weeks of wound healing after VMMC. This is in agreement with findings from a study conducted in Botswana [37]. Such inadequate knowledge may facilitate early resumption of sex [37,38], thus creating an opportunity for increased risk of transmission of HIV infection.…”
Section: Discussionsupporting
confidence: 90%
“…However, a significant proportion of the women in this study did not have adequate knowledge of the six weeks of wound healing after VMMC. This is in agreement with findings from a study conducted in Botswana [37]. Such inadequate knowledge may facilitate early resumption of sex [37,38], thus creating an opportunity for increased risk of transmission of HIV infection.…”
Section: Discussionsupporting
confidence: 90%
“…21 In a prior qualitative study, we found a lack of awareness of the increased risk of HIV acquisition during the wound healing period among Batswana men. 34 In our current study, nearly half of men reported HIV prevention as the primary reason for undergoing VMMC. Future intervention studies aiming to promote post-VMMC abstinence should emphasis HIV prevention messaging during wound healing and incorporate qualitative findings about how norms and attitudes drive men’s health promoting HIV preventative behaviors.…”
Section: Discussionmentioning
confidence: 56%
“…Our findings are similar to those of a study on AE patterns in Zimbabwe’s VMMC program, which found infections were more frequent in clients aged 10–14 years while bleeding was more frequent in clients aged ≥20 years [ 28 ]. More frequent bleeding in older clients could be related to increased vascularity of the penile skin, or to early resumption of sex following VMMC, which increases the risk of AEs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%